A Acessibilidade como veículo de inclusão social: proposta de dispositivo computacional para os deficientes visuais da cidade de Natal/RN - Santos Júnior, Zulmar Jofli dos (2009)
This study aims to propose a computing device mechanism which is capable to permit a tactile communication between individuals with visual impairment (blindness or low vision) through the Internet or through a local area network (LAN - Local Network Address). The work was developed under the research projects that currently are realized in the LAI (Laboratory of Integrated Accessibility) of the Federal University of Rio Grande do Norte. This way, the research was done in order to involve a prototype capable to recognize geometries by students considered blind from the Institute of Education and Rehabilitation of Blind of Rio Grande do Norte (IERC-RN), located in Alecrim neighborhood, Natal/RN. Besides this research, another prototype was developed to test the communication via a local network and Internet. To analyze the data, a qualitative and quantitative approach was used through simple statistical techniques, such as percentages and averages, to support subjective interpretations. The results offer an analysis of the extent to which the implementation can contribute to the socialization and learning of the visually impaired. Finally, some recommendations are suggested for the development of future researches in order to facilitate the proposed mechanism.